PENERAPAN MODEL MARKET PLACE UNTUK MENINGKATKAN KOGNITIF SISWA KELAS IV SDN 4 SIGLI - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to determine the application of the market place model can improve the cognitive learning of 4th grade students. The type of research used is Classroom Action Research (CAR). The subjects in this study were 16 of 4th grade students. Data collection techniques were carried out using observation sheets and test questions. The results of the study showed that in cycle I the average value obtained by students was 58 with a percentage of values ​​above the KKM of 33%. In cycle II students obtained an average value of 81.2 with a percentage of values ​​above the KKM reaching 89%. So it can be concluded that the application of the market place model can improve students' cognitive.